1965
DOI: 10.1017/s0016756800053218
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Structural Development of Israel and Adjacent Areas Since Upper Cretaceous Times

Abstract: The rifting of the Red Sea, the folding of the Zagros-Taurus range (in Turkey and Iran), and the development of the structures in and near Israel appear to have resulted from a northward anti-clockwise rotational movement of Arabia, which occurred in several phases during Upper Cretaceous to Pleistocene times. The sinistral strike slip fault of the Dead Sea Fault system participated in this movement. It is hereby suggested that the fold and fault structures in Israel and adjacent areas are drag effects along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(90 citation statements)
references
References 13 publications
4
86
0
Order By: Relevance
“…On the other hand, it is observed that the Ziqlag Formation and Beit Nir Conglomerate, take part in the main folding of the western flank of the Ramallah and Hebron anticlinoria. A similar situation for the Hazeva Formation is described from the eastern side of the Hebron anticlinorium (Freund, 1965). Thus, a much younger age has to be ascribed to this folding event.…”
Section: CL Folding In the Syrian Arcsupporting
confidence: 67%
“…On the other hand, it is observed that the Ziqlag Formation and Beit Nir Conglomerate, take part in the main folding of the western flank of the Ramallah and Hebron anticlinoria. A similar situation for the Hazeva Formation is described from the eastern side of the Hebron anticlinorium (Freund, 1965). Thus, a much younger age has to be ascribed to this folding event.…”
Section: CL Folding In the Syrian Arcsupporting
confidence: 67%
“…Lartet (1869) interpreted the movement along the Dead Sea Rift to be strike-slip as the major movement and normal as a minor one. This interpretation was subsequently supported by Quennel (1956 and, Freund (1965), Freund (1966 and1981), Freund et al (1968 and, Neev (1975), Bartov et al (1980), Garfunkel (1981) and Garfunkel et al (1981). Others (Vorman, 1961;Michelson, 1982;Bahat and Rabinovitch, 1983) claim that the rift evolved as a combination of vertical (dip-slip) and horizontal (left-lateral) movement.…”
Section: Introductionmentioning
confidence: 89%
“…Although the tectonic deformation of the region has been attributed to N-S relative motion along the Dead Sea Rift (e.g. Quennel, 1959;Freund, 1965), there are three schools of thought on the nature of movement along the Dead Sea Rift. Von Buch (1841) interpreted the Dead Sea Rift as a result of normal faulting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formed in the early Miocene, the DSTF transitions into the opening of the Red Sea (RS) Rift in the south to the Bitlis-Zagros collision zone of Arabia and Eurasia in the north [Quennell 1956, Freund et al 1968. Early Miocene geologic features are offset 105 km [Quennell 1956, Freund 1965, Bartov et al 1980, indicating that the long term sinistral slip rate of 4-6 mm/year is very similar to short term geodetic rate [Wdowinski et al 2004, Gomez et al 2007, Sadeh et al 2012. The DSTF in Israel and Jordan is divided into segments named according to the valleys, from south to north: the Araba Valley (AV), the Jordan Valley ( JV), and the Hula Valley (HV).…”
Section: Geology Seismotectonic Seismicitymentioning
confidence: 99%